1996
DOI: 10.1111/j.1476-5381.1996.tb15500.x
|View full text |Cite
|
Sign up to set email alerts
|

The vasoconstrictor effects of L‐NAME, a nitric oxide synthase inhibitor, in pregnant rabbits

Abstract: 1 We have used anaesthetized, acutely instrumented non-pregnant (NP) and late pregnant (P) New Zealand white rabbits to examine the possible role of nitric oxide (NO) in the pregnancy-induced fall of vascular tone and arterial pressure. Systemic, renal and pulmonary vascular resistance, as well as plasma concentrations of cyclic GMP (PcGMP) were compared before and after the inhibition of NO synthesis by N0-nitro-L-arginine methyl ester (L-NAME). 2 P rabbits had lower baseline total peripheral resistance (TPR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
2
6
1
Order By: Relevance
“…7]. Similar trends can be found in the other previous acute studies of cardiac output (8,16); in both cases, different conclusions would have been made depending on whether resistance or conductance changes were assessed.…”
Section: Importance Of Methods Of Data Analysissupporting
confidence: 69%
See 1 more Smart Citation
“…7]. Similar trends can be found in the other previous acute studies of cardiac output (8,16); in both cases, different conclusions would have been made depending on whether resistance or conductance changes were assessed.…”
Section: Importance Of Methods Of Data Analysissupporting
confidence: 69%
“…Only limited previous studies of the potential differential effects of NOS blockade on cardiac output and therefore total peripheral conductance or resistance have been performed. Studying acutely prepared, anesthetized rabbits, Losonczy et al (16) reported that L-NAME produced smaller absolute and percent increases in total peripheral resistance in pregnant rabbits and concluded that NO does not mediate the low vascular tone of pregnancy. Fiol et al (8) studied the effects of L-NAME in conscious ganglion-blocked pregnant and nonpregnant rats but failed to statistically compare between groups the effects of L-NAME on cardiac output or total peripheral resistance.…”
Section: Role Of No In the Global Vasodilation During Pregnancymentioning
confidence: 99%
“…Since intravascular¯ow is a substantial stimulus for endogenous NO synthesis (Miller & Vanhoutte, 1988) this may enhance the contribution of endogenous NO to renal vasodilatation in mid pregnancy. In contrast, in our experiments and those of Losonczy et al (1996), which were conducted close to term at 18 to 20 days gestation, renal blood¯ow and¯ow-induced changes in NO synthesis may have returned towards normal, leaving non-NO mediated mechanisms to predominate. Further investigations with animals at di erent gestational stages may help to clarify this issue.…”
Section: Discussioncontrasting
confidence: 43%
“…Our ®ndings and those of Losonczy et al (1996) di er in some respects from those of Danielson & Conrad (1995) for they used chronically instrumented, conscious 12 ± 14 day pregnant rats and showed that baseline glomerular ®ltration rate (GFR) and e ective renal plasma¯ow (ERPF) were signi®cantly increased, and e ective renal vascular resistance was decreased by 30 ± 40% compared with nonpregnant controls. Moreover, during acute infusion of L-NAME (2 ± 50 mg min 71 ) or N G -monomethyl-L-arginine (L-NMMA, 100 mg min 71 ), e ective renal vascular resistance, GFR and ERPF were equalized in pregnant and nonpregnant rats (the only exception being GFR during the 20 mg min 71 L-NAME infusion), because pregnant rats showed a greater decline in GFR, ERPF and elevation in e ective renal vascular resistance at each timepoint during the infusion of the NO synthesis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Animals had free access to standard rat chow and tap water. All experiments were approved by a govern-sure renal blood flow (RBF; Transonic Flowmeter 101, Transonic Systems, NY, NY, USA) [24]. Total peripheral mental committee on animal welfare.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%